Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To convert the given vertex form of the parabola equation [tex]\( y = (x - 3)^2 + 36 \)[/tex] into the standard form, we need to follow these steps:
1. Expand the squared term [tex]\((x - 3)^2\)[/tex]:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
2. Substitute the expanded form back into the equation:
[tex]\[ y = x^2 - 6x + 9 + 36 \][/tex]
3. Combine like terms:
[tex]\[ y = x^2 - 6x + 9 + 36 \][/tex]
[tex]\[ y = x^2 - 6x + 45 \][/tex]
So, the standard form of the equation is:
[tex]\[ y = x^2 - 6x + 45 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{A. \, y = x^2 - 6x + 45} \][/tex]
1. Expand the squared term [tex]\((x - 3)^2\)[/tex]:
[tex]\[ (x - 3)^2 = x^2 - 6x + 9 \][/tex]
2. Substitute the expanded form back into the equation:
[tex]\[ y = x^2 - 6x + 9 + 36 \][/tex]
3. Combine like terms:
[tex]\[ y = x^2 - 6x + 9 + 36 \][/tex]
[tex]\[ y = x^2 - 6x + 45 \][/tex]
So, the standard form of the equation is:
[tex]\[ y = x^2 - 6x + 45 \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{A. \, y = x^2 - 6x + 45} \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.